PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBASIS OUTDOOR STUDY UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR PADA MATA PELAJARAN IPAS DI KELAS V SD NEGERI 1 LANGGAR - Vonita Putri; Pamujo (STKIP Subang, 2024)
This study aims to enhance interest and academic achievement in science subjects using the Outdoor Study-based Problem Based Learning (PBL) model for fifth-grade students at SD Negeri 1 Langgar. The research employs a classroom action research (CAR) methodology, conducted over two cycles with two sessions in each cycle. The research procedure follows the Kemmis and Mc Taggart model, which includes the stages of planning, implementation, observation, and reflection. The subjects of this study are 20 fifth-grade students at SD Negeri 1 Langgar. Data collection instrumens include evaluation test sheets, teacher activity observation sheets, student activity observation sheets, questionnaries, and documentation. The results indicate that student interest in learning increased from 52,50% in the first cycle to 85,00% in the second cycle. Academic achievement also improved, with the average score rising from 67 and a mastery percentage pf 52.50% in the first cycle to an average score of 82 and a learning mastery percentage pf 92,50% in the second cycle. Based on these findings, it can be concluded that the Outdoor Study-based Problem Based Learning model can enhance both interest and academic achievement in science subjects for fifth-grade students at SD Negeri 1 Langgar.